Malaria Elimination in Iran, Importance and Challenges - Hemami, Mohsen Rezaei (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND: The aim of study is to assess the importance and challenges of Malaria elimination (ME) in Iran's health system. MATERIAL: Opinion of experts from Ministry of Health and Medical Education and the chancellors of medical universities affected by malaria were gathered using Focus Group Discussions and in-depth interviews. We asked them about the importance and main challenges of ME in Iran. RESULTS: Main factors on importance of ME were: it's a struggle to reach to equity in the poorest regions of county, prevention of emerging disease in susceptible regions, lowering the cost of control and its effects on the region's socioeconomic condition. Main challenges were Iran's long border with malaria-endemic countries Pakistan and Afghanistan and illegal immigrants, underdevelopment in rural areas, system's insensitivity and diagnosis problem due to reduction of cases. CONCLUSION: Quantitative and holistic researches are needed for assessing the consequences of ME.